Design of Location-Based Waste Collecting on Enviro Andalas Waste Bank - Husnil Kamil; Fajril Akbar; Mella Andriani (JOIV : International Journal on Informatics Visualization, 2019)
EnviroAndalas Waste Bank is engaged in worth selling dry waste management at Andalas University. Waste bank management activities include customer registration, waste bank transactions and picking-up of customer’s waste. The high number of customers and the transactions result in high workloads for the operators. During picking up customer’s waste, oftentlythe operator has difficulty in finding the pick-up location because the customer verbally gives the location instructions. Therefore the purpose of this study is to analyze, design, build, and test information systems for waste bank management at EnviroAndalasWaste Bank. The system development method used in this study is the waterfall method. In this study, the steps of the waterfall method used are requirements definitions, systems, and software design, implementation, and system testing. Application testing is carried out with black box testing and User Acceptance Testing (UAT) by the user. Blackbox testing of the functions has been in line with the initial system design and user requirements. This study resulted in web and mobile-based application on waste-bank management information system with location features that can be applied to the Enviro Andalas Waste Bank